Flat-topped NIR profiles originating from an unmixed helium shell in the Type IIb SN 2020acat. Issue 1 (14th October 2022) - Medler, K; Mazzali, P A; Ashall, C; Teffs, J; Shahbandeh, M; Shappee, B
ABSTRACT: The Near Infrared (NIR) spectra of the Type IIb supernova (SN IIb) SN 2020acat, obtained at various times throughout the optical follow-up campaign, are presented here. The dominant He i 1.0830 and 2.0581 μ m features are seen to develop flat-topped P-Cygni profiles as the NIR spectra evolve towards the nebular phase. The nature of the NIR helium peaks imply that there was a lack of mixing between the helium shell and the heavier inner ejecta in SN 2020acat. Analysis of the flat-top features showed that the boundary of the lower velocity of the helium shell was ∼3 − 4 × 10 3 km s −1 . The NIR spectra of SN 2020acat were compared to both SN 2008ax and SN 2011dh to determine the uniqueness of the flat-topped helium features. While SN 2011dh lacked a flat-topped NIR helium profile, SN 2008ax displayed NIR helium features that were very similar to those seen in SN 2020acat, suggesting that the flat-topped feature is not unique to SN 2020acat and may be the product of the progenitors structure.